Rapid estrogen and progesterone signaling to dendritic spine formation via cortactin/wave1-ARP2/3 complex - Uzair, Ivonne Denise (2019)
Synaptic plasticity is the neuronal capacity to modify the function and structure of dendritic spines (DS) in response to neuromodulators. Sex steroids, particularly 17β-estradiol (E2) and progesterone (P4), are key regulators in the control of DS formation through multiprotein complexes including WAVE1 protein, and are thus fundamental for the development of learning and memory. Objectives: The aim of this work was to evaluate the molecular switch Cdk5 kinase/PP2A phosphatase in the control of WAVE1 protein(phosphorylation/dephosphorylation) and the regulation of WAVE1 and cortactin to the Arp2/3 complex, in response to rapid treatments with E2 and P4 in cortical neuronal cells. Results: Rapid treatment with E2 and P4 modified neuronal morphology and significantly increased the number of DS. This effect was reduced by the use of a Cdk5 inhibitor (Roscovitine). In contrast, inhibition of PP2A with PP2A DN construct significantly increased DS formation, evidencing the participation of kinase/phosphatase in the regulation of WAVE1 in DS formation induced by E2 and P4. Cortactin regulates DS formation via Src and PAK1 kinase induced by E2 and P4. Both cortactin and WAVE1 signal to Arp2/3 complex to synergistically promote actin nucleation. Conclusion: These results suggest thatE2 and P4 dynamically regulate neuron morphology through non-genomic signaling via cortactin/WAVE1-Arp2/3 complex. The control of these proteins is tightly orchestrated by phosphorylation, where kinases and phosphatases are essential for actin nucleation and, finally, DS formation. This work provides a deeper understanding of the biological actions of sex steroids in the regulation of DS turnover and neuronal plasticity processes.